Teaching the scientific literature review collaborative lessons for guided inquiry - Schmidt, Randell K.; Smyth, Maureen M.; Kowalski, Virginia K. (Santa Barbara, California Libraries Unlimited, 2014)
"An essential resource for teachers and librarians who work with students in the later high school years through college and graduate school levels, this book explains and simplifies the scholarly task of researching and writing a scientific literature revie."--Provided by publisher.
Revision of: Lessons for a scientific literature review. 2008.
Includes bibliographical references (pages 167-169) and index.
Keywords: Scientific literature -- Study and teaching (Secondary).; Technical writing -- Study and teaching (Secondary).; Research -- Study and teaching (Secondary).; Peer review -- Study and teaching (Secondary).; Science publishing -- Study and teaching (Secondary).; Science -- Study and teaching (Secondary) -- Activity programs